Figure of Speech Stylistic Analysis on Selected Song Lyric in GUTS Album by Olivia Rodrigo - Zahara, Ayuna; Hidayat, Chatrine Aulia; Rangkuti, Rahmadsyah (Universitas Teknokrat Indonesia, 2024)
This study conducts a figure of speech stylistic analysis on selected song lyrics from Olivia Rodrigo's